ANALISIS INDEKS KEPUASAN MASYARAKAT TERHADAP KUALITAS LAYANAN JAKABARING SPORT CITY(JSC) PADA PENYELENGGARAAN EVENT OLAHRAGA DI KOTA PALEMBANG - Tri Astuti; Zunaidah Zunaidah; Rudy Noor Muktamar; Marlina Widiyanti (UNIB Press, 2020)
This study aims to find empirical evidence by analyzing the Community Satisfaction Index (IKM) on the service quality of the Jakabaring Sport City (JSC) in organizing sports events in Palembang City. This research is a quantitative descriptive research type with analysis techniques using the Community Satisfaction Index (IKM) which is based on KEPMENPAN Number: KEP / 25 / M.PAN / 2/2004. Respondents in this study were 152 people who held sports events in the Jakabaring Sport City environment. The distribution of questionnaires in this study was carried out by two methods, namely using google form media and distributing directly to the research sample based on data from sports event organizers at the JSC in 2019. The results of the calculation of the Community Satisfaction Index (IKM) in Jakabaring Sport City obtained a value of 71,472 which are in the interval 62.51 ? 81.25 so that the quality of their performance is in the